2016
DOI: 10.1016/j.vetpar.2015.12.023
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a novel oral formulation of sarolaner (Simparica™) against five common tick species infesting dogs in the United States

Abstract: The efficacy of a single oral treatment with sarolaner (Simparica™, Zoetis), a novel isoxazoline compound, was evaluated against five tick species known to infest dogs in the United States. A total of 10 laboratory studies, two against each species, were conducted using adult purpose-bred mongrels or Beagle dogs. In each study, 16 dogs were randomly allocated to one of two treatment groups based on pre-treatment host-suitability tick counts. Dogs were infested with approximately 50 unfed adult Amblyomma americ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 12 publications
1
19
0
Order By: Relevance
“…For instance, lotilaner efficacy was 100% against R. sanguineus and I. scapularis in at least 50% of post-treatment challenges. Another isoxazoline, sarolaner achieved similar results against these tick species, based on 48-h counts, through at least 1 month after treatment [ 13 ]. In contrast, afoxolaner, also an isoxazoline, did not achieve 100% efficacy 48 h after any post-treatment challenge in two studies with R. sanguineus [ 14 ] .…”
Section: Discussionmentioning
confidence: 99%
“…For instance, lotilaner efficacy was 100% against R. sanguineus and I. scapularis in at least 50% of post-treatment challenges. Another isoxazoline, sarolaner achieved similar results against these tick species, based on 48-h counts, through at least 1 month after treatment [ 13 ]. In contrast, afoxolaner, also an isoxazoline, did not achieve 100% efficacy 48 h after any post-treatment challenge in two studies with R. sanguineus [ 14 ] .…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy observed against A. cajennense in this study, 100% within 48 h of treatment of an existing infestation, and ≥ 99.6% within 48 h of weekly re-infestation for 35 days, is comparable with the efficacies reported for sarolaner against other tick species commonly found on dogs. Six et al [ 21 ] showed that sarolaner provided ≥ 99.6% efficacy within 48 h of treatment and ≥ 99.6% efficacy within 48 h after weekly re-infestation for 35 days against Amblyomma americanum , Amblyomma maculatum , Dermacentor variabilis , Ixodes scapularis and Rhipicephalus sanguineus . Similarly, Geurden et al [ 23 ] showed that sarolaner provided ≥ 99.7% efficacy within 48 h of treatment and ≥ 97.5% efficacy within 48 h after weekly re-infestation for 35 days against Dermacentor reticulaus , Ixodes hexagonus , I. ricinus and R. sanguineus.…”
Section: Resultsmentioning
confidence: 99%
“…This drug has high palatability and is fully and voluntarily consumed within 1 minute in 90.5% of cases (Becskei et al, 2016). No severe adverse effects were observed by earlier studies (Becskei et al, 2016;Mctier et al, 2016a;Six et al, 2016a;Six et al, 2016b).…”
Section: Introductionmentioning
confidence: 90%